THE TYPOLOGY OF THE LANGUAGE POLICY IN THE CONTEMPORARY CONDITIONS OF THE STATE DEVELOPMENT - Kovalova , T. (Pressing Problems of Public Administration, 2020)
The article gives a definition of the typology of the language policy, studies the typologies of the language policy represented in the works of science of native and foreign scientists, makes the generalization of the existing typologies. It also clarifies that the introduction of a certain type of the language policy depends on the range of factors, that is why it is necessary to research the current language situation in Ukraine as a set of demographic, social-linguistic and political parameters and define its similarity on each one to the countries where this policy was successful to make any conclusions about any type of it being appropriate for the Ukrainian situation.